Development of a Learning Module to Interpret Engineering Drawings Using Augmented Reality (AR) for Vocational High School Students - Zuhdi Mizian; Sofyan Sofyan; Saharrudin Saharrudin (STAI Hubbulwathan Duri, 2025)
Interpreting engineering drawings is a fundamental competency for vocational high school students preparing for industrial careers. However, conventional instruction often fails due to students’ difficulty in visualizing 3D objects from 2D representations, limited interactive learning tools, and low motivation. This study aimed to develop an Augmented Reality (AR)-assisted learning module to enhance the effectiveness and interactivity of engineering drawing instruction. The research employed the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model of Research and Development (RD), involving material experts, media specialists, instructional designers, teachers, and vocational students. The developed module was evaluated for feasibility and effectiveness. Expert assessments rated the module as